Effect of implant abutment material on peri-implant tissues: Narrative review - G. Sanjana; G. Priyanka; Ponsekar Abraham Anandapandian (SRM Journal of Research in Dental Sciences)
Introduction: The material of implant abutments plays a critical role in influencing the health and stability of peri-implant tissues. This structured review aims to evaluate the effect of commonly used abutment materials, including titanium, zirconia, and polymer-based composites, on peri-implant soft and hard tissues. Methods: A comprehensive review of existing clinical and in vitro studies was conducted to assess the biocompatibility, esthetic outcomes, bacterial adhesion, and influence on peri-implant mucosa and bone levels of various abutment materials. Results: Titanium has strong soft-tissue attachment and bacterial resistance, making it a reliable choice. Zirconia abutments exhibit superior esthetics and favorable soft-tissue integration, with the added advantage of lower bacterial adhesion. Meanwhile, polymer-based abutments provide good esthetics but may pose challenges in long-term stability and bone maintenance. Conclusion: Abutment material selection significantly influences peri-implant tissue health. Titanium and zirconia remain the preferred materials due to their balance of biocompatibility, strength, and soft tissue integration. Zirconia is particularly advantageous for esthetic zones, while titanium is suited for areas requiring high mechanical strength. Further research into advanced materials and surface modifications is needed to optimize outcomes for diverse clinical scenarios.